2016
DOI: 10.1038/pr.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variation in management and outcomes of very low-birth-weight infants with patent ductus arteriosus

Abstract: Use of cyclooxygenase inhibitors and ligation for PDA in VLBW infants decreased over a 10-y period at the studied hospitals. Further evidence is needed to assess the impact of this change in PDA management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 28 publications
3
63
2
Order By: Relevance
“…Their findings are similar to the results recently reported by Lokku et al (2) from the Canadian Neonatal Network and by Hagadorn et al (3) from the Pediatric Hospital Information System database. Although these studies demonstrate that there has been a decline in both the desire to investigate the presence of a PDA, as well as to treat it when present, they cannot tell us whether this trend toward “non-treatment” (or “conservative” management) has been applied primarily to infants with small, insignificant left-to-right PDA shunts or whether infants with moderate/large PDA shunts also have been included in this approach.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Their findings are similar to the results recently reported by Lokku et al (2) from the Canadian Neonatal Network and by Hagadorn et al (3) from the Pediatric Hospital Information System database. Although these studies demonstrate that there has been a decline in both the desire to investigate the presence of a PDA, as well as to treat it when present, they cannot tell us whether this trend toward “non-treatment” (or “conservative” management) has been applied primarily to infants with small, insignificant left-to-right PDA shunts or whether infants with moderate/large PDA shunts also have been included in this approach.…”
supporting
confidence: 92%
“…During the past decade, improvements in clinical care have been associated with a decrease in the incidence of neonatal morbidities that have not been causally linked to the persistence of a PDA (e.g., death, severe IVH, NEC and severe ROP) (1, 52). On the other hand, during the same period the incidence of BPD (which has been causally linked to the presence of a PDA (12, 13, 16, 49, 50)) has remained the same or even increased (1, 3, 52). Although many factors may contribute to the lack of improvement in the incidence of BPD, it is interesting to note that this has occurred during the same time interval that PDA treatment has been in decline (13, 52).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many infants are treated with medications in an attempt to close the PDA, and many others undergo surgical closure, usually after failed pharmacologic treatment [4]. Any treatment strategy should maximize efficacy and minimize toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study of 13 853 VLBW infants in the Pediatric Hospital Information System (PHIS) database found that use of interventions to close PDA decreased by 11% per year from 2005 to 2014 . This practice change was temporally associated with increases in unadjusted rates of bronchopulmonary dysplasia, periventricular leukomalacia, retinopathy of prematurity, and acute renal failure, but also with improved survival.…”
Section: Evidence From Population Surveysmentioning
confidence: 99%